The complete chloroplast genome of Lepidium latifolium linnaeus and phylogenetic analysis of brassicaceae. Issue 1 (2nd January 2021) - Shang, Shuai; Zhao, Liping; Xu, Tao; Li, Caiyun; Shen, Ruiting
Abstract: The complete chloroplast genome sequence of Lepidium latifolium Linnaeus was assembled and characterized in the present study. The plastome is 153, 989 bp in length, which is comprised of a large single-copy (LSC) region of 83, 565 bp, a small single-copy (SSC) region of 17, 526 bp, and two inverted repeat (IR) regions of 26, 449 bp. The overall GC content of the plastome was 36.5%. The new sequence comprised 125 genes, including 84 protein-coding genes, 8 ribosomal RNA genes, and 33 tRNA genes. Phylogenetic analysis showed that L. latifolium L. was close to Lepidium meyenii and Lepidium virginicum .